Irreversible Protein Labeling by Paal–Knorr Conjugation. (10th August 2017) - Dasari, Ramesh; La Clair, James J.; Kornienko, Alexander
Abstract: The application of new chemical reactions in a biological context has advanced bioconjugation methods for both fundamental research and commercial arenas. Recent adaptations of reactions such as Huisgen 1, 3‐dipolar or Diels–Alder cycloadditions have enabled the labeling of specific residues in biomolecules by the attachment of molecules carrying azides, alkynes, or strained alkenes. Although these are fundamental tools, there is a need for the discovery of reactions that can label native proteins. We report herein the adaptation of the Paal–Knorr reaction to label lysine residues in proteins via pyrrole linkages. Abstract : Labeling lysines : Recent advances toward a suite of bioorthogonal chemical reactions have profoundly enhanced the tools available to biochemists to study proteins and other biomolecules. Here, we describe the use of the Paal–Knorr reaction to fluorescently label proteins. The described procedures operate without reagents, catalysts, or organic solvents, as needed for a biocompatible method.